Hubungan Peran Orang Tua dengan Kemandirian Anak Retardasi Mental Di SLBN Dharma Asih Pontianak - Suriadi, Suriadi; Wardani, Nuniek Setyo; Fauzi, Muhammad (Jurnal Keperawatan dan Kesehatan, 2015)
Background: Mental health can be seen from the behavior of a person, because a person's behavior can beinterpreted differently by others, which depend on the values and beliefs. Many children who experiencemental health problems such as learning disorders, mental retardation (mild, moderate, severe and very severe), impaired motor skills and other disturbances, so that parents have a very important role in shaping the child's independence. Objective: To determine the role of parental relationship with a mentally retarded child interaction capabilities. Methods: This study used observational analytic design with cross sectional approach. Sampling technique is a non-probability sampling is the total sampling approach in accordance with the predetermined inclusion criteria and distributed to 82 respondents. To examine the relationship between independent and dependent variables using chi-analysis square Results: The results of the analysis showed no significant relationship between the roles of parents with mentally retarded child's independence with p value =0.000. Conclusion: There is a relationship between the roles of parents with mentally retarded children independence. So the role of independence in the elderly with special needs children is very important to improve children's skills and independence in children.